Clinical profile, management and outcomes of class IV emphysematous pyelonephritis in a tertiary care center: A retrospective descriptive study - R. Manjunath; M. Bennikal; S.K. Dasar; S.T. Patil (Ukrainian Journal of Nephrology and Dialysis, 2021)
Abstract. Class IV Emphysematous pyelonephritis (EPN) is a life-threatening infection of the kidney, and there is sparse data on immediate and long-term outcomes of medical management. The study aimed to review the clinical presentation, diagnosis, immediate and long-term outcomes of medical management, and outcome of patients presenting with class IV EPNMethods. This retrospective study was conducted in a tertiary care center in Dharwad, India. The study included class IV EPN patients admitted to the hospital between Jan 2012 to Dec 2019. The factors studied were demographics, comorbidities, radiological investigations, clinical presentation, urine, blood and pus culture, and sensitivity and treatment history. Immediate and long-term outcomes of medical management were determined. Descriptive analysis of the data was conducted. Continuous variables were presented as mean ± standard deviation and discrete variables in terms of number (%).Results. Twenty-one patients with class IV EPN, with a mean age of 55.7 ±13.5 years, were analyzed. The majority were males (M: F 15:6). The patients were followed up for 32.70±21.12 months. Fever, flank or abdominal pain, and acute kidney injury were observed in all 21 patients, while nausea and/or vomiting and dysuria were seen in 16 (76.2%) patients. E. Coli was the most common pathogen found. Double J stenting was done in 20 (95.2%) patients; Ultrasonography guided aspiration 8(38.1%) and percutaneous drainage in 5 (23.8%) patients. One (4.8%) patient died during the first episode and 3(19%) others due to recurrent infection and end-stage renal disease.Conclusions. Class IV Emphysematous pyelonephritis can be managed successfully by minimally invasive modalities. However, long-term morbidity and mortality risks are still negative.